Reforming Memory Essays on South African Church and Theological History - Vosloo, Robert (African Sun Media, 2017)
Although we should acknowledge the fragility of memory, we should nevertheless affirm the remarkable ability of memory to reform and transform our identity. Our memories and ways of remembering are, however, often marked by trauma and violence. Memory, therefore, not merely reforms; it too is in need of reformation, redemption and transformation. With this emphasis in mind, Reforming Memory grapples with the question what a responsible engagement with the past entails, also for Christians and churches associated with the Reformed tradition. The history of Reformed churches in South Africa is, one can argue, a deeply divided and ambivalent one. The same figures are heroes to some and villains to others; historic events are deeply ambiguous and conflicting views surround different discourses. Yet the histories, and perhaps futures, of these churches and traditions are inextricably interwoven. Reforming Memory fundamentally combines an interest in the notion of "memory" with an interest in (South African) Reformed theology and history. Central is the question: how should we remember and represent the past responsibly? The essays collected in this book engage in different ways with this question, attending in the process to some episodes in the history of the Dutch Reformed Church, some influential Reformed theologians, and some important Reformed practices and confessional documents.